Pengaruh Kualitas Pelayanan dan Citarasa terhadap Kepuasan Konsumen : Survei pada Konsumen M’DI Coffee In Cafe Tasikmalaya - Asda Nadya Santika; Depy Muhammad Pauzy; Suci Putri Lestari (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine and analyze the description of Service Quality, Taste and Consumer Satisfaction at M’DI Coffee in Cafe Tasikmalaya. The influence of service quality and taste simultaneously on consumer satisfaction at M’DI Coffee in Cafe Tasikmalaya and the effect of service quality and taste partially on consumer satisfaction at M’DI Coffee In Cafe Tasikmalaya. The method used in this research is quantitative with a survey approach. With a research sample of 100 consumers as respondents. The data used is primary and secondary data. The analytical tool used in this study is multiple linear regression using the SPSS version.25 support application. based on the results of the study, it is known that the quality of service and taste of consumer satisfaction at M’DI Coffee in Cafe Tasikmalaya is in a high classification. Service Quality and Taste have a significant effect simultaneously on customer satisfaction and Service Quality and Taste have a partially significant effect on customer satisfaction at M’DI Coffee in Cafe Tasikmalaya cafe.